Changes in Tear Film Characteristics in Patients With Idiopathic Dacryoadenitis. Issue 1 (January 2017) - Xue, Kang; Ren, Hui; Liu, Ailin; Qian, Jiang
Abstract : Purpose: To evaluate the tear-film meniscus with optical coherence tomography (OCT) in patients with idiopathic dacryoadenitis and to determine its relationships with the clinical tests. Methods: Sixteen patients with unilateral idiopathic dacryoadenitis were included in the study. Patients with idiopathic dacryoadenitis with affected sites (group 1), with contralateral sites (group 2) and healthy participants (group 3) completed the ocular surface disease index before optical coherence tomography determination of tear meniscus height and tear meniscus area. These were followed by measurements of tear breakup time, fluorescein staining, and Schirmer test. Finally, surgical debulking or incisional biopsies were conducted. Results: Tear meniscus height and tear meniscus area were the lowest in patients with affected sites (group 1) among the 3 groups ( p < 0.05). Breakup time was the shortest in group 1 ( p < 0.05). In the group 1, breakup time, fluorescein staining score, and histopathological phases were significantly correlated with tear meniscus height and tear meniscus area ( p < 0.05). Conclusions: Tear function was significantly disturbed in idiopathic dacryoadenitis. Tear menisci volumes measured by optical coherence tomography may assess the tearing function in patients with idiopathic dacryoadenitis. Abstract : We used optical coherence tomography (OCT) in patients with idiopathic dacryoadenitis to evaluate the tear–film meniscus. Tear function was significantly disturbed in idiopathic dacryoadenitis. But, Fluorescein staining score and histopathologic phase were significantly correlated with tear meniscus height (TMH) and tear meniscus area.